The Relationship between Knowledge and Physical Activity with Obesity in The Female Worker - Jaminah Jaminah; Trias Mahmudiono (Jurnal Berkala Epidemiologi, 2018)
Background: The prevalence of obesity in Indonesia had been reported as 14,80% in 2007, which found in female aged above 18 years old. This increased to 32,90% in 2013. Moreover, there were 102 female workers in the nutritional division of the public hospital Dr. Soetomo Surabaya in May 2016 reported being obese. Purpose: This study aimed to analyze the relationship between knowledge and physical activity with obesity in the female worker in nutritional division of RSUD Dr. Soetomo Surabaya. Methods: This analytical descriptive study design was cross sectional. There were 57 respondents selected through random sampling. Data were collected through questionnaire, anthropometrical measurement, and food recall. Data were analyzed through bivariate and multivariate tests. The relationship between the dependent and independent variable was investigated through cross tabulation and linear regression test. Results: Obesity nutritional status was 75,40%, poor nutritional knowledge was 90%, and moderate physical activity was 76%. There was a relationship between nutritional knowledge (p = 0,03) and physical activity (p = 0,03) with obesity. Meanwhile, the energy supply, protein, fat, and carbohydrate showed no correlation with the obesity (p > 0,37). Conclusion: There was a relationship between knowledge and physical activity on female workers of the nutritional division of RSUD Dr. Soetomo with obesity.